2019
DOI: 10.32479/irmm.7118
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The way online consumers assess the value of advertisements on social networking sites (SNSs) is important to know, because it has been shown that value of these advertisements can influence consumers' behavior toward advertised products and brands. In that regard, this study aimed to provide insights into how online consumers think about and assess the value of advertisements on SNSs by using a focus group method. Two focus groups were conducted with two groups from the different cultural background (Indian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The quantitative survey method dominates SMAR research, adopted by over 65% (n 5 60) of the articles identified. Including mixed-method studies, seven take qualitative approaches, such as focus group interview, in-depth interview, and semantic analysis (Deraz, 2019;Kongsagoonwong and Ngamkroeckjoti, 2018;Mattke et al, 2018a;Riedel et al, 2018; Note(s): One study published in 2020 is not included Truong and Simmons, 2010;Tsimonis et al, 2020;Youn and Kim, 2019a). Additionally, seven articles involve more than one study (Ahn et al, 2017;Belanche et al, 2017;Celebi, 2015;Hamby and Ilyuk, 2019;Huang, 2019;Park et al, 2016;Tsimonis et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative survey method dominates SMAR research, adopted by over 65% (n 5 60) of the articles identified. Including mixed-method studies, seven take qualitative approaches, such as focus group interview, in-depth interview, and semantic analysis (Deraz, 2019;Kongsagoonwong and Ngamkroeckjoti, 2018;Mattke et al, 2018a;Riedel et al, 2018; Note(s): One study published in 2020 is not included Truong and Simmons, 2010;Tsimonis et al, 2020;Youn and Kim, 2019a). Additionally, seven articles involve more than one study (Ahn et al, 2017;Belanche et al, 2017;Celebi, 2015;Hamby and Ilyuk, 2019;Huang, 2019;Park et al, 2016;Tsimonis et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive needs, affective needs, personal and social integrative needs and relaxation needs are considered fundamental "needs and gratification" categories (Ahmed and Raziq, 2017;Aydin, 2016Aydin, , 2018Celebi, 2015;Deraz, 2018Deraz, , 2019Gaber et al, 2019;Hassan et al, 2013;Miltgen et al, 2019;Taylor et al, 2011) Table A1. Theoretical foundations in the literature…”
Section: Appendixmentioning
confidence: 99%